Structure and Methylation of 35S rDNA in Allopolyploids Anemone multifida (2n = 4x = 32, BBDD) and Anemone baldensis (2n = 6x = 48, AABBDD) and Their Parental Species Show Evidence of Nucleolar Dominance - Mlinarec, Jelena; Boštjančić, Ljudevit Luka; Malenica, Nenad; Jurković, Adela; Boland, Todd; Yakovlev, Sonja Siljak; Besendorfer, Višnja (Frontiers in Plant Science, 2022)
Transcriptional silencing of 35S rDNA loci inherited from one parental species is occurring relatively frequently in allopolyploids. However, molecular mechanisms by which it is selected for transcriptional silencing remain unclear. We applied NGS, silver staining and bisulfite sequencing to study the structure, expression and methylation landscape of 35S rDNA in two allopolyploids of common origin, allotetraploid Anemone multifida (2n = 4x = 32, genome composition BBDD) and allohexaploid A. baldensis (2n = 6x = 48, AABBDD), and their progenitors, A. sylvestris (2n = 16, AA), A. cylindrica (2n = 16, BB) and A. parviflora (2n = 16, DD). The size of the recovered 35S rDNA units varied from 10489 bp in A. cylindrica to 12084 bp in A. sylvestris. Anemone showed an organization typical of most ribosomal 35S rDNA composed of NTS, ETS, rRNA genes, TTS and TIS with structural features of plant IGS sequences and all functional elements needed for rRNA gene activity. The NTS was more variable than the ETS and consisted of SRs which are highly variable among Anemone. Five to six CpG-rich islands were found within the ETS. CpG island located adjacent to the transcription initiation site (TIS) was highly variable regarding the sequence size and methylation level and exhibited in most of the species lower levels of methylation than CpG islands located adjacent to the 18S rRNA gene. Our results uncover hypomethylation of A. sylvestris- and A. parviflora-derived 35S rDNA units in allopolyploids A. multifida and A. baldensis. Hypomethylation of A. parviflora-derived 35S rDNA was more prominent in A. baldensis than in A. multifida. We showed that A. baldensis underwent coupled A. sylvestris-derived 35S rDNA array expansion and A. parviflora-derived 35S rDNA copy number decrease that was accompanied by lower methylation level of A. sylvestris-derived 35S rDNA units in comparison to A. parviflora-derived 35S rDNA units and inactivation of A. parviflora-derived 35S rDNA loci. These observations suggest that in A. baldensis nucleolar dominance is directed toward A. sylvestris-derived chromosomes. This work broadens our current knowledge of the 35S rDNA organization in Anemone and provides evidence of the progenitor-specific 35S rDNA methylation in nucleolar dominance.